Begonia tandangii (Begoniaceae, section Baryandra), a new species from Luzon Island, the Philippines - Nakamura, Koh; Rubite, Rosario Rivera; Kono, Yoshiko; Callado, John Rey; Peng, Ching-I (Phytotaxa, 2013)
We describe Begonia tandangii, a new species of Begonia sect. Baryandra from the Sierra Madre Mountain Range of Luzon Island, the Philippines. Begonia tandangii has a close resemblance to B. fenicis in gross morphology, differing in having leaf margin sparsely fringed with minute hairs (vs. glabrous or with minute hairs only on teeth) and capsules with broadly-ovate outline and an acuminate apex (vs. capsules with broadly-obovate outline and a rounded to truncate apex). Phylogenetic analyses of Philippines species of sect. Baryandra based on ITS sequences revealed that B. tandangii was clearly separated from B. fenicis. Begonia tandangii is currently known only from the type locality in a coastal forest of Baler, Aurora Province, which is in the neighborhood of Aurora Memorial National Park.